1992
DOI: 10.1159/000182551
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Adrenal-Like Tissue in a Patient with 17α-Hydroxylase Deficiency

Abstract: Testicular adrenal-like tissue (TALT) have been observed in patients with congenital adrenal hyperplasia, and is usually associated with 21-hydroxylase deficiency; in 3 cases with 11β-hydroxylase deficiency. We report a case of male pseudohermaphroditism with 17α-hydroxylase deficiency (17OHD) who also had TALT. To our knowledge, this is the first report about the association of 17OHD and TALT. Also, the patient had high levels of serum aldosterone – an unusual finding in patients with 17OHD. A possible pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…A total of 122 different CYP17A1 mutations have been described [Stenson et al, 2014]. To our knowledge, only 1 Spanish patient with a homozygous splice site mutation has been described to date [Perales Martínez et al, 2015], but others have been reported clinically [Garcia-Mayor et al, 1992]. It is possible that pediatric and adult patients can remain undiagnosed if the clinical and biochemical phenotypes are not adequately analyzed by experienced professionals.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 122 different CYP17A1 mutations have been described [Stenson et al, 2014]. To our knowledge, only 1 Spanish patient with a homozygous splice site mutation has been described to date [Perales Martínez et al, 2015], but others have been reported clinically [Garcia-Mayor et al, 1992]. It is possible that pediatric and adult patients can remain undiagnosed if the clinical and biochemical phenotypes are not adequately analyzed by experienced professionals.…”
Section: Discussionmentioning
confidence: 99%
“…A deficiência dos esteróides gonadais, por sua vez, determina a ausência de desenvolvimento dos caracteres sexuais secundários no paciente 46XX ou presença de pseudohemafroditismo masculino. Alguns aspectos relacionados à fisiopatologia da HAC por D17OH ainda não estão totalmente elucidados, como: 1) níveis elevados de aldosterona em alguns pacientes japoneses (76); 2) os possíveis casos de deficiência parcial da enzima, com genitália ambígua, menarca, níveis pressóricos ou de potássio dentro da normalidade; 3) definição clínica e laboratorial da deficiência isolada de 17,20 liase (77); e 4) a associação de achados fortuitos como restos de tecido adrenal em testículo (78), mielolipoma (79), adenoma adrenal (80), gônadas disgenéticas e desenvolvimento incompleto de ductos müllerianos (81).…”
Section: Hiperplasia Adrenal Congênita Por Deficiência De 17-hidroxilunclassified
“…Discrimination between cell types would not only be of great importance in dogs, but could also be helpful for the correct diagnosis of testicular tumours in man. For example, it can be difficult to distinguish histologically testicular adrenal rest tumours from Leydig cell tumours in patients that have congenital adrenal hyperplasia (Solish et al, 1989;Garcia-Mayor et al, 1992;Jódar-Gimeno et al, 1997). Furthermore, different areas of testicular stromal tumours may show an admixture of Leydig and Sertoli cells (Mostofi and Price, 1973) that could be recognized more easily using immunohistochemical markers.…”
mentioning
confidence: 99%